Analysis of Outcome-Based Education Curriculum Implementation: Focus of Study on Classical Mechanics Course - Taqwa, Muhammad Reyza Arief; Sinaga, Parlindungan; Suhendi, Endi; Rochintaniawati, Diana; Rahim, Handy Faishal (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2025)
The adoption of Outcome Based Education (OBE) curriculum in universities in Indonesia has been carried out massively, but in some cases, the implementation of OBE has not been carried out optimally, including in Classical Mechanics courses. The purpose of this study was to analyze (1) the suitability of the RPS document to the demands of Outcome-Based Education, (2) the implementation of lectures, (3) lecture evaluation mechanisms, and (4) the difficulties still experienced by students in the Classical Mechanics course. This research was conducted on 3 lecturers teaching Classical Mechanics courses and 64 undergraduate students of Physics Education at one of the universities in Malang. Data were collected through learning observation, interviews, surveys, and document analysis. Qualitative data analysis techniques using Miles & Huberman analysis techniques. The results showed that in general the implementation of the OBE-based curriculum in the Classical Mechanics course was good but there needed to be some improvements both in the RPS, learning implementation, and learning evaluation. On the other hand, there are still many difficulties experienced by students in understanding topics in Classical Mechanics lectures.